Anxiety in Language Testing: The APTIS Case (2017)
The requirement of holding a diploma which certifies proficiency level in a foreign language is constantly increasing in academic and working environments. Computer-based testing has become a prevailing tendency for these and other educational purposes. Each year large numbers of students take online language tests everywhere in the world. In fact, there is a tendency to use these tests more and more. However, many students might not feel comfortable when taking this type of exams. This paper describes a study regarding the fairly new APTIS Test (British Council). Thirty-one students took the test and responded to a structured online questionnaire on their feelings while taking it. Results indicate that the test brings a considerable amount of anxiety along with it.